Undergraduate Forensic Medicine & Toxicology Curriculum; Current Practices and Recommendations - Ansari, Rizwan Zafar; Yousaf, Muhammad; Abro, Farooq Ahmed; Abro, Farooq Ahmed; Khalil, ZahidHussain (International Journal of Pathology, 2018)
Forensic Medicine is an application of medical knowledge to solve legal problems. It is the branch of medical science which helps the law in searching for the truth to maintain justice in the society1. The main objective of teaching Forensic Medicine & Clinical Toxicology is to build the competencies of the undergraduate medical student for the interpretation of the community medico-legal, toxicological and ethical problems.2